2021
DOI: 10.1002/adfm.202105463
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Impact of Mg Substitution on the Properties of NASICON‐Na3+yV2−yMgy(PO4)3 Cathodes

Abstract: Vanadium multi-redox based NASICON-Na z V 2-y M y (PO 4 ) 3 (3 ≤ z ≤ 4; M = Al 3+ , Cr 3+ and Mn 2+ ) cathodes are particularly attractive for Na-ion battery applications due to their high Na insertion voltage (>3.5 V vs. Na + /Na 0 ), reversible storage capacity (~150 mA h g -1 ) and rate performance. However, their practical application is hindered by rapid capacity fade due to bulk structural rearrangements at high potentials involving complex redox and local structural changes. To decouple these factors, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
(110 reference statements)
0
9
0
Order By: Relevance
“…It is noted that the average discharge voltage of an NVP-Si cathode was ∼3.36 V, 50 mV higher than that of pristine NVP. Remarkably, both the power density and energy density of as-assembled Na||NVP cells are higher than those values for most reported NVP materials in recent publications [42][43][44][45][46][47] (Fig. 2b).…”
Section: Resultsmentioning
confidence: 53%
“…It is noted that the average discharge voltage of an NVP-Si cathode was ∼3.36 V, 50 mV higher than that of pristine NVP. Remarkably, both the power density and energy density of as-assembled Na||NVP cells are higher than those values for most reported NVP materials in recent publications [42][43][44][45][46][47] (Fig. 2b).…”
Section: Resultsmentioning
confidence: 53%
“…16 To further improve the energy densities of these ''alkali metal ion batteries'' (alkali metal = Li, Na, and K), novel electrode and electrolyte materials need to be discovered. 17,18 Previous research showed that layered materials could be promising anode candidates for alkali metal ion batteries (AMIBs). [19][20][21][22] These layered materials are composed of stacks of novel 2D materials like graphene, borophene, phosphorene, transition metal dichalcogenides (TMDs), transition metal carbides, and carbonitrides (MXenes), or their hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…16 To further improve the energy densities of these “alkali metal ion batteries” (alkali metal = Li, Na, and K), novel electrode and electrolyte materials need to be discovered. 17,18…”
Section: Introductionmentioning
confidence: 99%
“…16 To further improve the energy densities of these "alkali metal ion batteries" (alkali metal = Li, Na, and K), novel electrode and electrolyte materials need to be discovered. 17,18 Earlier research showed that layered materials could be promising anode candidates for alkali metal ion batteries (AMIBs). [19][20][21][22] These layered materials are composed of stacks of novel 2D materials like graphene, borophene, phosphorene, transition metal dichalcogenides (TMDs), transition metal carbides, and carbonitrides (MXenes), or their hybrids.…”
Section: Introductionmentioning
confidence: 99%